2011
DOI: 10.1177/0954405411413987
|View full text |Cite
|
Sign up to set email alerts
|

Heat transfer in hot stamping of high-strength steel sheets

Abstract: This paper focuses on the determination of the heat transfer coefficient (HTC) between blanks and dies in the hot stamping of high-strength steel sheets. Experiments to record the temperature evolution inside the dies were carried out on custom-built test equip- ment, where process conditions typical of hot stamping could be reproduced, but avoiding any deformation of the metal sheet. The HTC was determined by using an inverse analysis procedure, based on the comparison between temperature measured inside the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Significant variations have been observed in available data particularly in the conductivity for this tool material, and also noting that HTC is also sensitive to contact pressure which is difficult to measure experimentally. The Böhler-Edelstahl (2014) data sheet has reported the conductivity values of 26-29.2 W/m K in the temperature range of 100-700 • C, while Tondini et al (2011) have reported the value of 42.2 W/m K.…”
Section: Conductivitymentioning
confidence: 97%
“…Significant variations have been observed in available data particularly in the conductivity for this tool material, and also noting that HTC is also sensitive to contact pressure which is difficult to measure experimentally. The Böhler-Edelstahl (2014) data sheet has reported the conductivity values of 26-29.2 W/m K in the temperature range of 100-700 • C, while Tondini et al (2011) have reported the value of 42.2 W/m K.…”
Section: Conductivitymentioning
confidence: 97%
“…Although the internal heat transfer mechanism of organic fibrous materials is complex at the microscopic scale, where radiation and convection mechanisms among fibres take place, it can be adequately described at the observation scale by means of effective heat conduction coefficients (27). Also the thin air film in-between the substrate can be modelled at the macroscopic scale assuming a thin thermally resistive layer which insulates the heat conduction through the different layers (28). According to KASHIWAGI and NAMBU (29), cellulosic substrate shows three different reactions during thermal oxidative degradation.…”
Section: Governing Equationsmentioning
confidence: 99%
“…Active research aimed at solving such problems is currently focused on the hot stamping process. [1][2][3][4][5] Research on martensite formation according to temperature, 6 effects of the forming parameters in a hot process 7 and effects of spring back and residuals on the product 8 have been reported. Although hot stamped products have high stiffness, they are used restrictively in components requiring collision absorption because of their low elongation.…”
Section: Introductionmentioning
confidence: 99%